Pruning SMAC search space based on key hyperparameters - Li, Hui; Liang, Qingqing; Chen, Mei; Dai, Zhenyu; Li, Huanjun; Zhu, Ming (Concurrency and computation, 2022)
Summary Machine learning (ML) has been widely applied in many areas in recent decades. However, because of its inherent complexity and characteristics, the efficiency and effectiveness of ML algorithm often to be heavily relies on the technical experts' experience and expertise which play a crucial role to optimize hyperparameters of algorithms. Generally, the procedure tuning the exposed hyperparameters of ML algorithm to achieve better performance is called Hyperparameters Optimization. Traditional hyperparameters optimization methods are manually exhaustive search, which is unavailable for high dimensional search spaces and large datasets. Recent automated sequential model‐based optimization led to substantial improvements for this problem, whose core idea is fitting a regression model to describe the importance and dependence of algorithm's performance on certain given hyperparameter setting. Sequential model‐based algorithm configuration (SMAC) is a the‐state‐of‐art approach, which is specified by four components, Initialize, FitModel, SelectConfigurations, and Intensify. In this article, we propose to add a pruning procedure into SMAC approach, it quantifies the importance of hyperparameters by analyzing the performance of a list of promising configurations and reduces search space by discarding noncritical and bad key hyperparameters. To investigate the impact of pruning for model's performance, we conducted experiments on the configuration space constructed by Auto‐Sklearn and compared the effect of run time and pruning ratio with our algorithm. The experiments results verified that, our method made the configuration selected by SMAC more stable and achieved better performance.